2013
DOI: 10.1038/jcbfm.2013.209
|View full text |Cite
|
Sign up to set email alerts
|

Aneurysmal Remodeling in the Circle of Willis after Carotid Occlusion in an Experimental Model

Abstract: Carotid occlusions are associated with de novo intracranial aneurysm formation in clinical case reports, but this phenomenon is not widely studied. We performed bilateral carotid ligation (n ¼ 9) in rabbits to simulate carotid occlusion, and sham surgery (n ¼ 3) for control. Upon euthanasia (n ¼ 3 at 5 days, n ¼ 6 at 6 months post ligation, and n ¼ 3 at 5 days after sham operation), vascular corrosion casts of the circle of Willis (CoW) were created. Using scanning electron microscopy, we quantified gross morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 39 publications
3
29
0
Order By: Relevance
“…In particular, the curvature of the parent vessel has been shown to play a role in aneurysm formation, as well as aneurysm growth and possible progression to rupture. Experiments on animal models showed that increased vessel tortuosity preceded aneurysm formation following bilateral carotid ligation in rabbit models (Tutino et al, 2014). Following analysis on 3D synthetic models of curved arteries, Foutrakis et al (1999) and Hoi et al (2004) theorized that high hemodynamic stress is responsible for the formation of aneurysms on the lateral outer wall of the curved bends.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the curvature of the parent vessel has been shown to play a role in aneurysm formation, as well as aneurysm growth and possible progression to rupture. Experiments on animal models showed that increased vessel tortuosity preceded aneurysm formation following bilateral carotid ligation in rabbit models (Tutino et al, 2014). Following analysis on 3D synthetic models of curved arteries, Foutrakis et al (1999) and Hoi et al (2004) theorized that high hemodynamic stress is responsible for the formation of aneurysms on the lateral outer wall of the curved bends.…”
Section: Discussionmentioning
confidence: 99%
“…A similar change was reported in a model of cerebral aneurysm in rabbits. 13 The MRA technique tested in this study appears to be sufficiently accurate and reproducible for future preclinical studies in mice. Representative serial magnetic resonance images of a mouse with aneurysmal subarachnoid hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…These images were compared to electron micrographs of rabbit casts prepared in the same manner in a previous study. (5)…”
Section: Introductionmentioning
confidence: 99%